TRITON X-100 AND DMSO INDUCED CELL PERMEABILITY FOR THE RELEASE OF CAMPESTEROL AND FLAVONOIDS IN CULTURED CELLS OF BLUMEA LACERA (BURM. F.) DC - PRIYANKA PATADE; VIJAY D. MENDHULKAR; MOINUDDIN VAKIL (International Journal of Pharma and Bio Sciences, 2017)
Triton X-100 and Dimethyl sulfoxide (DMSO) were used as permeabilizing agent for the release of campesterol and flavonoids in cell suspension culture of Blumea lacera. The permeabilizing treatment with both the agents (Triton X-100 and DMSO) in Blumea lacera cell culture revealed interesting results indicating appropriate selection and administration of treatment protocol i.e. concentrations and treatment durations. Triton X-100 (1%) for 4 hr treatment duration favored high release of flavonoids (0.096 mg/g) (3.0 fold) as compared to control (0.032 mg/g) in suspension cultures of Blumea lacera. For Campesterol, 0.1% Triton X-100 treatment for 4 hr duration showed marked enhancement (2.092 mg/g, 6.0 fold) over respective control (0.346 mg/g). DMSO treatment with 0.4% concentration and 6 hr duration induced 2.5 fold release in both flavonoids (0.025 mg/g) and Campesterol (0.201 mg/g) in comparison with their respective control.